2007
DOI: 10.1007/s00468-007-0190-7
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal changes in photoprotective mechanisms of leaves from shaded and unshaded field-grown coffee (Coffea arabica L.) trees

Abstract: Coffee is native to shady environments, but often grows and yields better without shade. Thus, it may be reasoned that coffee leaves should display enough plasticity to acclimate themselves to contrasting light environments. However, little is known about mechanisms associated with such plasticity in coffee. This work aimed, therefore, to explore differences in leaf photoprotective mechanisms. Plants were grown in the field and received either 48 or 100% natural light. Evaluations were made using outer leaves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
61
2
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(75 citation statements)
references
References 42 publications
9
61
2
3
Order By: Relevance
“…On the other hand, a high planting density may increase the intensity of the competition. In trees, the increase in the chlorophyll pigment and the decrease of the Chl a/Chl b ratio are characteristics of the shaded leaves (Sarijeva et al 2007;Chaves et al 2008;Lichtenthaler et al 2013). In this study, the high light compensation point and chlorophyll pigment content and a low Chl a/Chl b ratio clearly suggested that there were light limitations for plant growth under a high planting density.…”
Section: Discussionmentioning
confidence: 52%
“…On the other hand, a high planting density may increase the intensity of the competition. In trees, the increase in the chlorophyll pigment and the decrease of the Chl a/Chl b ratio are characteristics of the shaded leaves (Sarijeva et al 2007;Chaves et al 2008;Lichtenthaler et al 2013). In this study, the high light compensation point and chlorophyll pigment content and a low Chl a/Chl b ratio clearly suggested that there were light limitations for plant growth under a high planting density.…”
Section: Discussionmentioning
confidence: 52%
“…A decrease in Ψ has been related to a drop in the photochemical eff iciency of PSII (DemmigAdams et al, 1989;Epron et al, 1992). In addition, in the hottest days, one-year old seedlings showed the lowest Φ PSII values, related to the low Fv/Fm and as an indirect inference of its increased capacity to dissipate excess excitation energy (Chaves et al 2008); while the oldest seedlings (class 4) showed the highest Φ PSII values.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors (Friend, 1984;Fahl et al, 1994;Morais et al, 2003;Nascimento et al, 2006;Araújo et al, 2008;Gomes et al, 2008;Chaves et al, 2008) observed an increase in the photosynthetic rate of coffee plant leaves under high radiation when compared with exposed shaded leaves. However, other authors found that coffee plants under shading present higher CO 2 assimilation (Nutman, 1937;Kumar & Tieszen, 1980;Freitas et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…An increase in the net assimilation of CO 2 was observed in coffee plant leaves under high radiation when compared with shaded leaves exposed to lower radiation (Friend, 1984;Fahl et al, 1994;Morais et al, 2003;Nascimento et al, 2006;Araújo et al, 2008;Gomes et al, 2008;Chaves et al, 2008). Nevertheless, other authors found that coffee plants under shading present higher photosynthetic rates (Nutman, 1937;Kumar & Tieszen, 1980;Freitas et al, 2003).…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation